Quantifying treatment system resilience to shock loadings in constructed wetlands and denitrification bioreactors. (1st August 2018) - Sukias, James P.S.; Park, Jason B.K.; Stott, Rebecca; Tanner, Chris C.
Abstract: Wastewater treatment ecotechnologies such as constructed wetlands and denitrifying bioreactors are commonly perceived as robust and resilient to shock loading, but this has proved difficult to quantify, particularly when comparing different systems. This study proposes a method of quantifying and comparing performance resilience in response to a standard disturbance. In a side-by-side study we compare the treatment performance of four different configurations of wetlands and denitrifying bioreactors subjected to hydraulic shock loads of five times the standard inflow rate of primary treated sewage for five days. The systems consist of: horizontal-flow gravel-bed wetlands (HG); single pass vertical-flow sand or gravel media wetlands followed by carbonaceous denitrifying bioreactors (VS + C and VG + C respectively); and a recirculating anoxic attached-growth bioreactor and vertical sand media wetland followed by carbonaceous denitrifying bioreactors (R(A + VS)+C). Resilience was quantified for Total Suspended Solids (TSS), Five-day Biochemical Oxygen Demand (BOD5 ) and Total Nitrogen (TN) by time integration of Relative Disturbance in Performance relative to pre-shock loading performance (days equivalent Performance Reduction), and by the Recovery Time after shock loading ceased. The quantification method allowed an unbiased comparison of the four different systems. It highlighted important differences in the resilience for different removal mechanisms associated with the configuration of the wetlands/bioreactor systems. Relative Disturbances in Performance were expressed in comparison to percent daily removal under standard loading, and, for the different pollutants were equivalent to loss of between 0.08 and 2.51 days of removal capacity. Average Recovery Times ranged from zero to three days, with all systems exhibiting substantial recovery even during the five-day shock loading period. This study demonstrated that both the horizontal gravel wetland and the vertical flow wetland systems combined with carbonaceous bioreactors tested are generally resilient to shock loading of five times hydraulic and organic loading for periods of up to five days. Standard quantification of performance resilience to shock loadings or other perturbations has potential application across a wide range of technologies and research fields. Graphical abstract: Highlights: Resilience of ecotechnologies under shock-loading was quantified and compared. Average recovery times ranged from zero to three days after 5 days of shock loadings. Horizontal gravel system had least resilience to shock-loadings for key contaminants. Vertical-flow wetland and bioreactor systems showed minimal performance reduction.